Influence of Additional Acid Etch Treatment on Resin Cement Dentin Infiltration - Mary P. Walker, MS, DDS,1 Yong Wang, PhD,2 James Swafford, MS,3 Adrian Evans,4 (Blackwell Synergy, 2000)
The purpose of this study was to compare the penetration of a resin cement into dentin surfaces pretreated with self-etching primer with or without conventional acid etch.